Reconstructing Mining Licensing Policy with an Emphasis on Water Resource Protection: A Case Study of PDAM Water Pollution in Bangka Regency - Suhendra, Hendra; Junaidi Abdillah (Universitas Muhammadiyah Surabaya, 2025)
The high incidence of PDAM water pollution in Bangka Regency is a central issue in this study, indicating a weakness in mining licensing policies and water resource protection. This research aims to analyze the legal framework related to mining licensing and to assess the urgency of reconstructing these policies to prevent ongoing water pollution. The research method used is normative and empirical juridical, examining various laws and regulations such as Law No. 3 of 2020 on Mineral and Coal Mining, Law No. 32 of 2009 on Environmental Protection and Management, and Law No. 17 of 2019 on Water Resources. In addition, field data was collected through a case study in Bangka Regency. The findings indicate that despite the existence of regulations, their implementation and oversight remain ineffective, particularly in terms of synergy between mining management agencies and environmental protection bodies. Therefore, a more comprehensive reconstruction of licensing policies is needed, integrating environmental protection as a priority and strengthening inter-agency coordination to create sustainable and responsible mining governance.